Performance metrics in the Pharmaceutical Supply Chain (PSC) - Ali, Osman (2016)
Supply Chain Management (SCM) is a concept that is gaining popularity and importance. There is little confirmation if SCM is particularly important and what role it plays in organisations working with each other. This dissertation looks at if medication shortages be reduced through the following questions: •Which metrics are used in the supply chain management of pharmaceutical supply chain? In addition, how effective or efficient are they? •What relevant information metrics is taking place in the supply chain management of the pharmaceutical chain? Furthermore can it be analysed qualitative and quantitatively? •What are the enablers and inhibitors in this process